1,3-thiazole Derivatives: A Scaffold with Considerable Potential in the Treatment of Neurodegenerative Diseases - Chaudhary, Jasmine; Jain, Akash; Dhingra, Ashwani; Chopra, Bhawna; Sharma, Vishal; Gupta, Jatin; Kaushik, Aditi (Current Topics in Medicinal Chemistry, 2023)
1,3-thiazoles, which contain nitrogen and a sulfur atom is an unsaturated five-membered heterocyclic ring, have achieved a unique significant place in drug design and development because of their versatile structure and a variety of pharmacological activities, viz. anticancer, antiviral, antimicrobial, anticonvulsant, antioxidant, antidiabetic, etc. They have inspired researchers to design novel thiazole with different biological activities. The presence of the thiazole moiety has resulted in a large number of clinically useful drugs with a wide range of activities, such as Ritonavir (antiviral), Sulfathiazole (antimicrobial antibiotic), Abafungin, Ravuconazole (antifungal), Meloxicam (NSAID), etc., that further verify this statement. The prevalence of neurodegenerative diseases like Alzheimer's, Parkinson's, and Huntington’s is increasing at a rapid pace but existing treatments mainly provide symptomatic relief and are associated with undesired effects. Consequently, designing novel compounds with more effectiveness and reduced toxicity are required. 1,3-thiazole derivatives have emerged as excellent candidate in this regard and have an important role for the treatment of neurodegenerative diseases. In the current review, we have gathered all the appropriate literature which demonstrate the remarkable role of 1,3-thiazole and its derivatives in these diseases that may help design new compounds with more desired characteristics. The literature was assessed through worldwide scientific databases like GOOGLE, SCOPUS, and PUBMED using different keywords, and only relevant information published in English was evaluated.
Keywords: Parkinson